1998
DOI: 10.1111/1467-8535.00056
|View full text |Cite
|
Sign up to set email alerts
|

A holistic approach to supporting distance learning using the Internet: transformation, nottranslation

Abstract: This is the first of a series of papers describing how the Open University, a large distance education institution, has embraced the Internet as a medium for supporting its students, tutors, academics, and administrators throughout the education process. This paper reports on a holistic approach to integrating technology into the teaching process which addresses how to provide necessary functions in effective formssome traditional, some new. It describes the development and structure of actual systems, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 9 publications
(11 reference statements)
0
30
1
Order By: Relevance
“…The British Open University's early experiences revealed that a critical mass of online participants was essential for quality online interaction. The British Open University's experiences also revealed the tutors' central role as an active participant and facilitator, a human factor necessary for successful online learning outcomes (Thomas et al, 1998). Other research carried out at the British Open University (Price and Petre, 1997) indicated that students engaged in the online tutoring sessions, were:…”
Section: Supporting Students Using Internet Technologiesmentioning
confidence: 97%
“…The British Open University's early experiences revealed that a critical mass of online participants was essential for quality online interaction. The British Open University's experiences also revealed the tutors' central role as an active participant and facilitator, a human factor necessary for successful online learning outcomes (Thomas et al, 1998). Other research carried out at the British Open University (Price and Petre, 1997) indicated that students engaged in the online tutoring sessions, were:…”
Section: Supporting Students Using Internet Technologiesmentioning
confidence: 97%
“…Benefits may include provision for disadvantaged students as well as cost savings through economies of scale or automation of the teaching processes; also, embracing video, audio and animation may help the learning process (Stephenson, 2001). E-learning is a term applied to systems for distance learning (Rudenstein, 1998), software to support students taking a campusbased course, or simply online documentation for teaching (O'Hagan, 1998;Thomas et al, 1998). Online learners rely on Internet connections to communicate with institutions, tutors and other learners, and there is often a sense of isolation from the support of others.…”
Section: Online Learningmentioning
confidence: 99%
“…Benefits may include provision for disadvantaged students as well as cost savings through economies of scale or automation of the teaching processes, also embracing video, audio and animation may help the learning process (Stephenson, 2001). E-learning is a term applied to systems for distance learning (Rudenstein, 1998), software to support students taking a campus-based course, or simply online documentation for teaching (Thomas, Carswell et al, 1998;O'Hagan, 1998). Online learners rely on Internet connections to communicate with institutions, tutors and other learners, and there is often a sense of isolation from the support of others .…”
Section: Online Learningmentioning
confidence: 99%
“…Indeed technology has the potential to change the ways in which we teach and support students in the traditional university beyond recognition (Laurillard, 1993). There are difficulties in providing online tutorial support for students, and a particular problem is how students online can gain the same learning experiences as traditional campus based students (Thomas, Carswell et al, 1998).…”
Section: Introductionmentioning
confidence: 99%